Sill emplacement during rifting and inversion from threedimensional seismic and well data, Phitsanulok Basin, Thailand - Songwoot Naviset (2018)
The Cenozoic Phitsanulok rift basin (Thailand) is extensively affected by igneous intrusions and lava flows. In the Ruang Thong-Sai Ngam area, the E-A01 well drilled the early Miocene synrift Lan Krabu Formation, and unexpectedly encountered a 300-m-thick olivine dolerite sill (sill 3). The top and base of the sill are characterized by medium- to low-amplitude contrasts, atypical for most (high amplitude) responses from intrusions. Seismic interpretation, artificial neural networks, and model-based inversion were used to understand the seismic response of the intrusions. Two key factors combined to mask sill 3: (1) stacking of common depth point gathers resulted in lower amplitudes at the top and base of the sill, and (2) multiple intruded sills separated by thin shales caused internal reflectivity. Using the sill geometries, sill stratigraphic position, and inferred magma flow directions from broken bridges, an estimate of the relative timing of the sills, and the local stress orientations at the time of displacement was made. Three sills are inferred to have been emplaced during the Miocene when the maximum horizontal stress direction (Shmax) was north-south and two were emplaced during the Miocene when the stress direction was approximately east-west. Such orientations are compatible with known phases of Miocene inversion (east-west Shmax) and extension (northsouth Shmax), although local stress changes associated with igneous bodies could also explain rotation to an east-west Shmax.